The reliability, validity and sensitivity of an individualised sub-maximal fitness test in elite rugby league athletes - Scott, T. J.; McLaren, S. J.; Lovell, R.; Scott, M. T. U.; Barrett, S. (Journal of Sports Sciences, 2022)
We aimed to examine the reliability, validity and sensitivity of an individualised sub-maximal fitness test (SMFTIFT60). Nineteen elite rugby league players performed a one-week test-retest of SMFTIFT60. Typical Errors and ICCs were: small (<3.5%) and extremely high (>0.90) for accelerometer-derived variables; moderate (<2.5% points) and moderate to very high (0.71-0.89) for exercise and recovery heart rate (HRex and HRR, respectively). Convergent validity correlations with the 10-week pre-season change in 30-15 Intermittent Fitness Test performance were large for changes in SMFTIFT60 HRex (r = -0.57) and HRR (0.60), and very large for changes in accelerometer measures (range: -0.71 to -0.79). For sensitivity, within-player dose-response relationships between SMFTIFT60 HRex and prior 3-day training loads were negative and ranged from moderate (session ratings of perceived exertion [sRPE-TL], r = -0.34), to large (high-speed running distance, -0.51; acceleration load, -0.73) and very large (heart rate Training Impulse [TRIMP], -0.83). All other relationships were unclear or trivial to small. Physiological and accelerometer-derived measures from the SMFTIFT60 are reliable and valid for the assessment of fitness in rugby league players. Only HRex appears sensitive to acute changes in training load. The SMFTIFT60 could be a useful monitoring tool in team sports